Peripheral nerve conduits: technology update - Arslantunali D (Dove Medical Press, 2014)
D Arslantunali,1–3,* T Dursun,1,2,* D Yucel,1,4,5 N Hasirci,1,2,6 V Hasirci,1,2,7 1BIOMATEN, Center of Excellence in Biomaterials and Tissue Engineering, Middle East Technical University (METU), Ankara, Turkey; 2Department of Biotechnology, METU, Ankara, Turkey; 3Department of Bioengineering, Gumushane University, Gumushane, Turkey; 4Faculty of Engineering, Department of Medical Engineering, Acibadem University, Istanbul, Turkey; 5School of Medicine, Department of Histology and Embryology, Acibadem University, Istanbul, Turkey; 6Department of Chemistry, Faculty of Arts and Sciences, METU, Ankara, Turkey; 7Department of Biological Sciences, Faculty of Arts and Sciences, METU, Ankara, Turkey *These authors have contributed equally to this work Abstract: Peripheral nerve injury is a worldwide clinical problem which could lead to loss of neuronal communication along sensory and motor nerves between the central nervous system (CNS) and the peripheral organs and impairs the quality of life of a patient. The primary requirement for the treatment of complete lesions is a tension-free, end-to-end repair. When end-to-end repair is not possible, peripheral nerve grafts or nerve conduits are used. The limited availability of autografts, and drawbacks of the allografts and xenografts like immunological reactions, forced the researchers to investigate and develop alternative approaches, mainly nerve conduits. In this review, recent information on the various types of conduit materials (made of biological and synthetic polymers) and designs (tubular, fibrous, and matrix type) are being presented. Keywords: peripheral nerve injury, natural biomaterials, synthetic biomaterials